E-Commerce in the Development of Modern Digital Economy: Advantages and Challenges - Hanifah, Miftah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
E-commerce is the trade of products or services conducted using the internet. The purpose of writing this article is to determine the classification of e-commerce business models, the advantages of e-commerce, the disadvantages of e-commerce, and the challenges of e-commerce to deepen knowledge about e-commerce. E-commerce has become a very important component in the development of the modern digital economy, providing easy accessibility and efficiency for consumers and business actors. Through various business models that suit transaction needs, e-commerce expands market coverage and provides added value through easy access and excellent utilization of consumer data. The successful implementation of e-commerce requires more attention, especially to the security of personal data. Overall, e-commerce has a very important role in the development of an adaptive and sustainable digital economy in this modern era.